Analysis of Effects of Solar Irradiance, Cell Temperature and Wind Speed on Photovoltaic Systems Performance - Al-Bashir, Adnan; Al-Dweri, Mohamed; Al-Ghandoor, Ahmad; Hammad, Bashar; Al-Kouz, Wael (International Journal of Energy Economics and Policy, 2019)
This paper proposes an analytical model to investigate the effects of solar irradiance, cell temperature and wind speed on performance of a photovoltaic system built at the Hashemite University, Jordan. The system is off–grid connected with the azimuth and tilt angles are being changed periodically and manually. The model has been developed employing Multivariate Linear Regression to estimate generated power based on experimental data. The methodology of building the model is demonstrated and validated for its accuracy using Analysis of Variance. The model indicated that a linear relationship among predicting parameters and generated power is valid agreeing with many other reported studies. In addition, the model emphasizes the independency of these predicted parameters; the model indicates that there is no correlation between the predictors themselves. The effect of each predicted parameter also found in agreement with the well-known relationship between each parameter and predicted power through algebraic signs. It is found that the model predicts generated power with R2 values of 96.5% with the solar irradiance being the most effective parameter. Due to the low wind speed for the geographical location where the experiment carried out, its effect according to the model is not significant. Keywords: Photovoltaic Systems, Irradiance, Cell Temperature, Wind Speed, Multivariate Linear Regression, Modeling, Simulation JEL Classifications: C1, C3, C6, O3 DOI: https://doi.org/10.32479/ijeep.8591